The Effect of Financial Development on Income Inequality in Iran: Structural Vector Auto-Regression Approach - Mohammad Ali Motafakkerazad; Ahmad Assadzadeh; mahdi sheykhmaollayi (پژوهشهای اقتصادی, 2019)
Income distribution is of crucial importance for policymakers from the social justice viewpoint.  In recent years, financial tools and intermediaries have been developed in the global economy. Thus, investigating the impact of financial development on the income inequality has attracted the attention of economic researchers. Financial development affects income distribution through both channels of economic growth (directly) and increasing access to financial services (indirectly). Many studies have been conducted regarding the effects of financial development on income distribution in Iran with different methods and indicators, and even contradictory results. This study analyzes the effect of financial development on income inequality using various indicators and the structural vector auto-regression (SVAR) approach. The findings confirm the direct effect of financial development on income inequality, or the inequality-narrowing hypothesis, though they have no decisive implication on the indirect effects of financial development on income inequality, or the inequality-broadening hypothesis.